A Sensitive Signal‐off Electrochemical Aptasensor for Thrombin Detection using PB−Au@MoS2 Nanomaterial as Both Platform and Signal Reporter. Issue 2 (13th May 2021) - Wu, Chao; Zhang, Qiaran; Li, Duo; Tang, Xuehui; Xie, Fei; Zhang, Yue; Lu, Yizhong
Abstract: Human serum is one of the effective samples for point‐of‐care testing (POCT). Sensitive and quick determination of thrombin content in human serum samples is important. An electrochemical aptasensor based on Prussian blue and Au nanoparticles loaded MoS2 nanoflowers (PB−Au@MoS2 ) hybrid was constructed. By using PB−Au@MoS2 as both a substrate and a signal reporter, this aptasensor could demonstrate excellent performance for thrombin detection with a detection linear range from 0.01 pM to 30 nM and detection limit down to 1 fM. This work may provide a strategy to establish effective and sensitive sensing devices for thrombin in clinical diagnosis. Abstract :